The Spirit shaped church : a Spirit ecclesiology in India - Bar, Swarup (Minneapolis, MN : Fortress Press, 2021)
"In The Spirit Shaped Church, Swarup Bar argues that the church is defined by its relationship with others. A relational church depends on the porousness of its borders, which means that, while a church has its distinctiveness, it ought to be open to negotiate relational engagements with the world around it. This sort of relationally distinct, permeable church is found to be possible through the leading of the Spirit and the work of Christ. Such engagement is found to be relevant in a plural, religio-cultural context and in situations of marginalization in India. The Spirit Shaped Church reflects an ongoing commitment on the part of Fortress Press to engage the needs of Christian communities around the world. The book is aimed at teachers, clergy, students, and anyone with an interest in the lived experience of Christians in India."--Publisher
Plural contexts, marginalised communities: ecclesial challenges in India -- The church and its pneumatological shape with permeable borders: exploring Western paradigms -- The shape of the church: overview of Indian ecclesiological conversations -- The spirit shaped church: ecclesiologies of select Indian thinkers -- Implications of a permeable spirit ecclesiology for select issues in India.
Includes bibliographical references (pages 225-249) and index.
Keywords: Church; Christianity -- India; Holy Spirit; Christianisme -- Inde; Saint-Esprit.; Holy Spirit; Christianity; Church; India